2013
DOI: 10.1007/s10803-013-1924-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysregulation During Sensory Stimulation in Children with Autism Spectrum Disorder

Abstract: Autonomic nervous system (ANS) activity during sensory stimulation was measured in 59 children with autism spectrum disorder (ASD) ages 6-9 in comparison to 30 typically developing controls. Multivariate comparisons revealed significant differences between groups in the respiratory sinus arrhythmia (parasympathetic measure) vector of means across sensory stimuli (p = 0.02) and in change from domain to domain (p = 0.01). Sympathetic activity, measured by pre-ejection period, did not differ significantly between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 50 publications
2
60
0
Order By: Relevance
“…In one large study, Schaaf et al (2013) examined vagal activity of 59 children with autism and 30 typical controls in response to a variety of sensory stimuli, such as auditory, tactile, and olfactory signals. The vector of means across stimuli differed across the groups, with a flatter vector of mean scores in the autism group suggesting that these individuals demonstrated blunted autonomic change from one condition to the next.…”
Section: Behavioral and Genetic Correlates Of Cardiac Activity: Withimentioning
confidence: 99%
“…In one large study, Schaaf et al (2013) examined vagal activity of 59 children with autism and 30 typical controls in response to a variety of sensory stimuli, such as auditory, tactile, and olfactory signals. The vector of means across stimuli differed across the groups, with a flatter vector of mean scores in the autism group suggesting that these individuals demonstrated blunted autonomic change from one condition to the next.…”
Section: Behavioral and Genetic Correlates Of Cardiac Activity: Withimentioning
confidence: 99%
“…The SNS is responsible for mobilizing resources to respond to challenges or threats [Beauchaine, 2001;Sheppes, Catran, & Meiran, 2009], whereas the PNS is involved in slowing heart rate and reducing arousal through increased output along the vagus nerve [Beauchaine, 2015a;Benevides & Lane, 2015]. To date, research on children with ASD has predominantly focused on the SNS or the PNS in isolation, with only a few studies measuring both systems concurrently [e.g., Bujnakova et al, 2016;Cohen, Masyn, Mastergeorge, & Hessl, 2015;Levine et al, 2012;Neuhaus, Bernier, & Beauchaine, 2016;Schaaf, Benevides, Leiby, & Sendecki, 2015]. Extending this work by considering interactions between the SNS and PNS increases the specificity with which psychophysiological responses can be characterized, and enhances comprehensive conceptualization of the role of autonomic activity in the manifestation of behavioral pathology [Buss, Jaffee, Wadsworth, & Kliewer, 2018;El-Sheikh et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in regulatory systems that underlie social approach and avoidance behavior, including alterations in the ANS, could be related to observable differences in social behavior in ASD (Benevides and Lane, 2013). Impedance cardiography may be particularly beneficial in assessing ANS reactivity in ASD; it is non-invasive and can act as an objective measure of reactivity to a variety of stimuli (Schaaf, Benevides, Leiby, & Sendecki, 2015). Despite the benefits of impedance cardiography both methodologically and empirically, there have been few ASD studies that utilize PEP.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of impedance cardiography both methodologically and empirically, there have been few ASD studies that utilize PEP. One study found that children with ASD did not have significantly different changes in PEP compared to controls following a sensory challenge (Schaaf et al, 2015). In another study, which asked participants to interact with a novel adult and with a parent, children with ASD demonstrated disorganized ANS responses.…”
Section: Introductionmentioning
confidence: 99%